2008
DOI: 10.2514/1.35737
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Spanwise Pitch on Local Heat Transfer for Multiple Jets with Crossflow

Abstract: The influence of spanwise jet-to-jet spacing on local heat transfer distribution due to multiple impinging circular air jets from an in-line rectangular array on a surface parallel to the jet plate is studied experimentally. The length-todiameter ratio of the nozzles of the jet plate is 1.0. The flow, after impingement, is constrained to exit in one direction from the confined passage formed between the jet plate and the target plate. Mean jet Reynolds numbers based on the nozzle-exit diameter d covered are 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The analysis revealed an optimal jet to target distance for maximum heat transfer between 2D and Sd, with 3D being considered a good initial design value. Likewise to Katti and Prabhu [34], an optimal spanwise spacing of 4D was also found. Van Treuren [28.29] studied three different jet to target ratios, 1D, 2D, and 4D.…”
Section: Inline Impinging Arrayssupporting
confidence: 55%
See 3 more Smart Citations
“…The analysis revealed an optimal jet to target distance for maximum heat transfer between 2D and Sd, with 3D being considered a good initial design value. Likewise to Katti and Prabhu [34], an optimal spanwise spacing of 4D was also found. Van Treuren [28.29] studied three different jet to target ratios, 1D, 2D, and 4D.…”
Section: Inline Impinging Arrayssupporting
confidence: 55%
“…The experimental work of Katti and Prabhu [34] investigates the effect of spanwise spacing on the heat transfer distribution. Their analysis reveals that the non-uniformity in jet flow and non-linearity of the channel flow increases with decreasing jet to target spacing and spanwise pitch.…”
Section: Inline Impinging Arraysmentioning
confidence: 99%
See 2 more Smart Citations
“…The jet fountain is an important factor affecting the heat transfer characteristics when multi-jet impingement is considered. Katti and Prabhu [15] experimentally investigated the effect of different span-wise pitches on the local heat transfer coefficient distribution on the plate by an array of multi-jet impingement. Their study showed that a span-wise pitch of 4 times diameter of hole performs better than that of 2 or 6 times, according to the analysis of the Nu and the pressure loss coefficient.…”
Section: Introductionmentioning
confidence: 99%